Utility of Tuberculin Testing in Children Under 5 Years of Age - B.N. Gaind; A.M. Berry; S. Ghosh (Paediatrica Indonesiana, 1983)
The usefulness of the tuberculin sensitivity in children as an index of tuberculosis was evaluated in terms of the conversion index. Out of 62 children, 27 had abnormal X-rays. Family surveys lead to picking up of nine children who had radiological evidence of the disease. Lymph node biopsy in one of the subjects showed tuberculous lymphadenitis. How relevant this index of tuberculin conversion is as an indicator of tuberculous disease in childhood is clear from the present study. It is an important procedure for screening and can considerably reduce the work load and increase case yield. It also gives us a good idea about the prevalence and epidemiology of tuberculous infection in children.